Generalized Vehicle Dynamics. - Williams, Daniel (SAE International, 2022)
An industry professional with more 30 years of experience in chassis control systems from concept to launch, Daniel Williams brings this experience and his unique approach to readers of Generalized Vehicle Dynamics.